The Effect of QR Code-Assisted Adventure-Based Learning on Students’ Cognitive Learning Outcomes in Atmospheric Science - Umi Fauziah; Febrian Andi Hidayat; Mivtha Citraningrum; Mursalim Mursalim; Ihsan Ihsan; Jurianto As (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2026)
This study compared changes in Grade X students’ cognitive learning outcomes after atmospheric-material instruction using QR code-assisted Adventure-Based Learning (ABL) and conventional instruction. A quasi-experimental nonequivalent pretest–posttest control-group design involved 36 students from SMA Muhammadiyah Al-Amin, Sorong City, selected purposively from two intact classes. Cognitive outcomes were measured using a 20-item multiple-choice test. The available aggregate data were analyzed descriptively through mean scores, raw gain, and normalized gain. The experimental-class mean increased from 57.2 to 85.4 (raw gain = 28.2; N-gain = 0.66), whereas the control-class mean increased from 55.8 to 73.2 (raw gain = 17.4; N-gain = 0.39). Thus, the experimental class achieved a 10.8-point larger raw gain and a 0.27 higher N-gain. These results provide descriptive evidence that integrating QR-linked multimedia and contextual group challenges within ABL may strengthen students’ understanding of atmospheric concepts. Inferential conclusions require the reporting of individual scores, standard deviations, and complete statistical-test results